2005
DOI: 10.1524/ract.2005.93.11.683
|View full text |Cite
|
Sign up to set email alerts
|

Resistance, accumulation and transformation of selenium by the cyanobacterium Synechocystis sp. PCC 6803 after exposure to inorganic SeVI or SeIV

Abstract: Our purpose was to investigate the ability of Synechocystis sp. PCC 6803, a photosynthetic prokaryote isolated from fresh water, to resist, incorporate and reduce the oxidized forms of selenium including selenite and selenate, the major selenium species present in aquatic systems. Selenium speciation and the chemical intermediates during selenium transformation were determined by X-ray absorption near edge structure (XANES) spectroscopy. The possible internalisation pathways involving selenium and the metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Indeed, various studies have demonstrated that selenate uptake in some microorganisms, such as E. coli , yeast , and Synechocystis sp. , is mediated by a sulfate transporter. Therefore, when the metabolized sulfur in transferred onto an organic moiety such as L‐cysteine or L‐cystine, competition between sulfur and selenium does not occur.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, various studies have demonstrated that selenate uptake in some microorganisms, such as E. coli , yeast , and Synechocystis sp. , is mediated by a sulfate transporter. Therefore, when the metabolized sulfur in transferred onto an organic moiety such as L‐cysteine or L‐cystine, competition between sulfur and selenium does not occur.…”
Section: Discussionmentioning
confidence: 99%
“…The amounts correspond to mg g À1 (name of the element in bold) or mM l À1 (italic). These experimental concentration limits are obtained during EXAFS studies except for the Se, V and two of the Cr experiments (Chaurand et al, 2007;Rose, Cornu et al, 2007;Gouget et al, 2005; XANES studies). Open circles: Bakkaus et al 2009 experiments presented in this paper the Si(444) reflection was chosen.…”
Section: Figurementioning
confidence: 98%
“…The cyanobacterium Synechocystis sp. accumulated almost 10% of initial 0.3 mg L −1 selenate concentration, and selenite accumulation reached almost 34% without selenium volatilization . Kagami et al reported efficient selenium(VI) biovolatilization by bacterium Pseudomonas stutzeri under aerobic conditions.…”
Section: Introductionmentioning
confidence: 99%